Forward modelling of the Montagna dei Fiori fault-related fold (Central Apennines, Italy), using combined kinematic models - Di Francesco, L.; Fabbi, S.; Santantonio, M.; Poblet, J.; Bigi, S. (TRABAJOS DE GEOLOGÍA, 2009)
The Montagna dei Fiori has received attention by geologists through the past decades because of both its Jurassic stratigraphy and its complex present-day structure. The latter is the result of multiple phases of deformation, from the Early Jurassic, during the rift phase, which led to the opening of the Tethyan Ocean, to compression in Neogene, linked with the evolution of the Apennines fold and thrust belt. In this paper, we present a new stratigraphic interpretation of the Jurassic palaeogeography, based on a new geological mapping project in the area. Using this new stratigraphy, we constructed two forward models of the Montagna dei Fiori fault-related fold, using a combination of different kinematic models. We followed two different approaches: the first model was constructed manually starting from the construction of a balanced cross section and its restoration, followed by a definition of the main steps for the forward model; the second was constructed using 2DMove (Midland Valley), starting from a simplified version of the same stratigraphy and using the same main steps imposed in the other section.